Inorganic mercury in mammary cells: viability, metal uptake but efflux?. Issue 1 (February 2018) - Maniero, Mariángeles; Guerrero-Gimenez, Martin; Fanelli, Mariel; Wuilloud, Rodolfo
Abstract The viability, cellular uptake and subcellular distribution of heavy metal Hg, were determined in human mammary cell lines (MCF-7, MDA-MB-231 and MCF-10A). It was observed that Hg had the capacity of being excluded from the cells with a different type of possible transporters. MCF-7 cells showed the lowest viability, while the other two cell lines were much more resistant to Hg treatments. The intracellular concentration of Hg was higher at lower exposure times in MCF-10A cells and MCF-7 cells; but as the time was increased only MDA-MB-231 showed the capacity to continue introducing the metal. In MCF-7 and MCF-10A cells the subcellular distribution of Hg was higher in cytosolic fraction than nucleus and membrane, but MDA-MB-231 showed membrane and nucleus fraction as the enriched one. The analysis of RNA-seq about the genes or family of genes that encode proteins which are related to cytotoxicity of Hg evidenced that MCF-10A cells and MCF-7 cells could have an active transport to efflux the metal. On the contrary, in MDA-MB-231 no genes that could encode active transporters have been found.